Implementation of The Development of Balas Klumprik Grand Forest Park, Surabaya : English - Nisa Hafi Idhoh Fitriana; Alifia Salma Az Zahra; Attar Yusuf Alvero; Sekar Jasmine (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Balas Klumprik Grand Forest Park (Tahura) in Surabaya plays a strategic role in environmental conservation, ecological education, and urban sustainability. Amidst the rapid urbanisation of Surabaya, this forest park is designed to function as an integrated green space that combines conservation, education, and recreation. This study aims to comprehensively analyse the implementation of development strategies in the park, identify the challenges faced during their execution, and explore the potential for future optimisation. A qualitative descriptive method was used, supported by primary and secondary data obtained through interviews, observations, and documentation. The results show that development efforts are translated into programs such as horticultural cultivation, plant propagation, and digital promotion. However, the implementation still faces challenges, including limited financial and human resources, low public participation, lack of infrastructure, and pressures from surrounding urban development. Despite these constraints, Tahura Balas Klumprik has strong ecological and social potential to become a centre of educational ecotourism and a hub for community-based environmental empowerment. This study provides several recommendations, including innovation in educational tourism programs, infrastructure improvements, and digitalization. Strengthening multi-stakeholder collaboration and sustainable management is essential to maximize the park’s role in supporting the Sustainable Development Goals (SDGs), particularly goals 11 and 15. Contribution to Sustainable Development Goals (SDGs):SDG 11: Sustainable Cities and CommunitiesSDG 15: Life on Land